A Novel Spectrophotometric Method for Determination of Histamine Based on Its Complex Reaction with Ni(II) and Alizarin Red S - Miftakhul Jannatin; Ganden Supriyanto; Pratiwi Pudjiastuti (Indonesian Journal of Chemistry, 2017)
The development of analytical methods of histamine using Ni (II) and alizarin red S reagents by UV-Vis spectrophotometry has been done. The objective of this research is to determine the ability of Ni(II) and alizarin red S to form color complex compound with histamine and it will be used to detect the presence of histamine qualitatively and quantitatively as well. Absorbance was measured at a maximum wavelength of 604 nm. In this method, it has been carried out optimization of analytical parameters such as the concentration of Ni(II), the concentration of alizarin red S, pH, and respond time. Analytical parameter optimization showed concentration of Ni(II) is 20 ppm, alizarin red S 75 ppm, pH 8, and a respond time of 15 minutes. Method validation indicated that the coefficient of variation, detection limit, and the limit of quantitation are 0.245%; 9.49 ppm; and 31.62 ppm respectively with a sensitivity of 0.0063/ppm and linearity of 0.99. Accuracy to histamine with a concentration of 50, 75, and 125 ppm are 105.87%, 101.06%, 97.21%, respectively.